2009
DOI: 10.1177/1073191109340383
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Construct Validity of the Relationship Profile Test: Associations With Physical Health and Anaclitic and Introjective Traits

Abstract: The authors examined the construct validity of the Relationship Profile Test (RPT) with respect to measures of two related constructs-physical health and well-being (functional health status), and depression-linked personality type (anaclitic vs. introjective). In Study 1, the authors administered the RPT, Depressive Experiences Questionnaire (DEQ), and Medical Outcomes Study Short Form (MOS SF-20) to 116 undergraduate students. In Study 2, the RPT, DEQ, and MOS SF-20 were administered to 110, mostly African A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…DD was not significantly correlated with many of the scales of the PAI, and showed smaller magnitude correlations with the SCL-90-R scales than did DO. This latter result was unexpected and could be related to DD’s lower internal reliability; however, when the internal consistency reliabilities of this study are compared to the past 12 RPT studies reporting Cronbach’s alpha values, internal consistency reliability, (Bornstein et al, 2003; Bornstein et al, 2004; Bornstein et al, 2009; Bornstein et al, 2010; Denkle et al, 2011; Denkle et al, 2015; Haggerty et al, 2010; Haggerty et al, 2012; Huprich et al, 2010; Hutchins & Raith, 2014; Porcerelli et al, 2009; Porcerelli et al, 2015) the present values are not much different from previously reported reliabilities (average Cronbach alphas for DO, DD and HD for these 12 studies are .82, .72, .74 respectively).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…DD was not significantly correlated with many of the scales of the PAI, and showed smaller magnitude correlations with the SCL-90-R scales than did DO. This latter result was unexpected and could be related to DD’s lower internal reliability; however, when the internal consistency reliabilities of this study are compared to the past 12 RPT studies reporting Cronbach’s alpha values, internal consistency reliability, (Bornstein et al, 2003; Bornstein et al, 2004; Bornstein et al, 2009; Bornstein et al, 2010; Denkle et al, 2011; Denkle et al, 2015; Haggerty et al, 2010; Haggerty et al, 2012; Huprich et al, 2010; Hutchins & Raith, 2014; Porcerelli et al, 2009; Porcerelli et al, 2015) the present values are not much different from previously reported reliabilities (average Cronbach alphas for DO, DD and HD for these 12 studies are .82, .72, .74 respectively).…”
Section: Discussionmentioning
confidence: 54%
“…We compared RPT scores to scores on two well-validated and widely used broadband measures of psychopathology, the Personality Assessment Inventory (Morey, 1991) and the Symptom Checklist-90-Revised (Derogatis, 1994) as well as a short-form of the Experiences in Close Relationships Scale (Wei, Russell, Mallinckrodt, & Vogel, 2007), a dimensional measure of adult attachment. Past research on the construct validity of the RPT found that the Destructive Overdependence (DO) and Dysfunctional Detachment (DD) scales were negatively correlated with measures of psychological health and attachment security, and positively correlated with measures of psychopathology and attachment insecurity (Bornstein & Huprich, 2006; Bornstein, Porcerelli, Huprich, & Markova, 2009; Haggerty et al, 2010, 2012; Huprich, Hsiao, Porcerelli, Bornstein, & Markova, 2010). The present study seeks to extend these results using different measures, and in a different population—patients with substance use disorders.…”
mentioning
confidence: 99%
“…Second, the majority of our a priori hypotheses with respect to associations between RPT subscales and criterion variables were in expected directions and suggest a heretofore unexplored association between dependency, coping, and health behaviors among conjugally bereaved adults. Results contribute to extant findings of the construct validity of the RPT among various populations and samples, including low-income urban women (Bornstein et al, 2009; Porcerelli et al, 2009), psychotherapy patients (Huprich et al, 2010), substance-abuse patients (Bornstein, Gottdiener, & Winarick, 2010), and college students (Bornstein et al, 2002; Haggerty et al, 2010). …”
Section: Discussionmentioning
confidence: 75%
“…Finally, because previous studies have noted that individuals high in HD demonstrate more adaptive health behaviors (Huprich, Hsiao, Porcerelli, Bornstein, & Markova, 2010; Porcerelli et al, 2009), we expected to find a negative association between somatic complaints and HD.…”
Section: Aims and Hypothesesmentioning
confidence: 95%
“…Although there is conflicting evidence regarding the consequences of social loss among overly dependent individuals (Bonanno et al, 2002; Overholser, 1990), we hypothesized that our findings would be consistent with those in the literature linking dependency on the spouse with subsequent prolonged grief (Bonanno et al, 2002; Prigerson, Maciejewski, & Rosenheck, 2000). Finally, dysfunctional detachment (DD) is associated with social isolation and withdrawal (Birtchnell, 1987) poor health outcomes (Huprich, Hsiao, Porcerelli, Bornstein, & Markova, 2010) and difficulties in social and occupational functioning (Kantor, 1993). Because studies suggest that social isolation may compound grief reactions (Dyregrov, Nordanger, & Dyregrov, 2003) we hypothesized that DD would also be linked with prolonged grief.…”
Section: Introductionmentioning
confidence: 99%